Activation of the kynurenine pathway is associated with striatal volume in major depressive disorder. (December 2015) - Savitz, Jonathan; Dantzer, Robert; Meier, Timothy B.; Wurfel, Brent E.; Victor, Teresa A.; McIntosh, Scott A.; Ford, Bart N.; Morris, Harvey M.; Bodurka, Jerzy; Teague, T. Kent; Drevets, Wayne C.
Highlights: The ratio of kynurenic acid (KynA) to quinolinic acid (QA) was reduced in MDD. KynA/QA was not associated with striatal volume in the MDD group. Activation of the kynurenine pathway was associated with striatal volume in MDD. Abstract: Inflammation, which may be present in a subgroup of individuals with major depressive disorder (MDD), activates the kynurenine metabolic pathway to produce kynurenine metabolites kynurenic acid (KynA) and quinolinic acid (QA). We have previously reported an association between the ratio of KynA to QA and hippocampal volume in MDD. In animals, inflammation leads to deficits in incentive motivation. Given the central role of the nucleus accumbens (NAcc) and other regions of the striatum in motivated behavior, reward processing, and anhedonia, we hypothesized that abnormalities in the concentrations of kynurenine pathway metabolites would be associated with striatal volumes. As previously reported, after controlling for relevant confounds, the KynA/QA ratio was reduced in the serum of unmedicated patients with MDD ( n  = 53) versus healthy controls (HC, n  = 47) and there was a non-significant trend in the correlation between KynA/QA and severity of anhedonia ( r  = −0.27, p  < 0.1). There was no significant difference between the MDD and HC groups in any of the individual kynurenine metabolites or volume of the striatum defined as the sum of the volumes of the NAcc, caudate, and putamen. After regressing out the effects of sex, analysis batch, and supratentorial volume, the kynurenine concentration and the ratio of kynurenine to tryptophan were inversely associated with striatal volumes in the MDD sample ( p  < 0.05, uncorrected). Further, striatal volume was correlated with the items, "concentration difficulties", "lassitude", and "pessimism" from the Montgomery-Asberg Depression Rating Scale. Our results raise the possibility that activation of the kynurenine pathway is a marker of an inflammatory process that leads to reductions in striatal volume. However, unlike the hippocampus, the association does not appear to be mediated by the relative balance between KynA and QA.